ALGAL STUDY IN SPRINGS AND STREAMS IN SHAQLAWA DISTRICT, ERBIL PROVINCE-IRAQ III- CHLOROPHYCEAE WITHOUT ZYGNEMATALES - Janan. J. Toma,; Farhad. H. Aziz, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Freshwater algae (Chlorophyceae-except Zygnematales) were collected from 18 sites (12 springs and 6 streams) in Shaqlawa district within Erbil Province, Kurdistan Region of Iraq from September-2019 to August-2020. Aim of this study isolation and identification new algal species. 27 new algal genera with 40 species records at first time in Kurdistan Region and others provinces of Iraq, which include the following, Scenedesmus considered the most abundance than others algae which seven species identified followed by genus of Chlamydomonas, genus of Chlorophyceae, genus of Characium with three species for each one recorded, but genera Geminella have two species, finally the remaining genera have one species identified for each one